A MANAJEMEN PEMELIHARAAN SARANA PRASARANA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SDIT SUBULUSSALAM RAMAN UTARA LAMPUNG TIMUR - Sahroni; Abidin, Muhammad Zainal (Universitas Muhammadiyah Metro, 2025)
This research examines the management of school infrastructure maintenance in improving learning quality at SDIT Subulussalam Raman Utara, East Lampung. The study aims to analyze the infrastructure maintenance management process, assess learning quality improvement, and identify implementation barriers and solutions. The research employs a qualitative approach with descriptive analytical design, involving nine informants selected through purposive sampling. Data collection was conducted through participatory observation, in-depth interviews, and documentation studies. The findings reveal the implementation of maintenance management through three stages: collaborative-based planning, implementation with routine and periodic maintenance patterns, and systematic evaluation. Infrastructure maintenance positively correlates with learning quality in psychological, pedagogical, and administrative dimensions. Major constraints include budget limitations, structural damage, lack of technological facilities, and low digital competencies among educators. Mitigation strategies encompass developing external collaborative networks, enhancing educator capacity, reorienting budget priorities, and implementing participatory maintenance approaches.